EFFECTIVENESS AND PHARMCOKINETICS OF FIRST-LINE ANTI TUBERCULOSIS DRUGS IN CHILDREN: A SYSTEMATIC REVIEW - M. Hadi, (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: The optimal doses of first-line drugs for treating drug-susceptible tuberculosis in children and adolescents are still uncertain.Aim: The purpose of this study was to determine whether children treated with recommended or increased doses of first-line drugs achieve successful outcomes and adequate pharmacokinetic (PK) exposures. Methods: A systematic search strategy was conducted across several electronic reference databases (PubMed, Cochrane Library, Google Scholar) and included articles published between 2010–2023. Duplicate publications, review articles, editorials, and incomplete articles were excluded.Results: Database searches identified a total of 59.123 articles. Of these, 300 articles passed the screening process, resulting in 47 articles for full-text assessment. Among them, 28 articles did not evaluate the outcome of interest. Hence, we found 19 appropriate studies included.Conclusion: The outcomes are highly variable. Children have lower drug exposures than adults. Rifampicin exposure is inadequate for younger infants and/or those with HIV. For optimal administration, standardisation of pharmacokinetic paediatric studies and individual patient data analysis with safety assessment are required.